2018
DOI: 10.1021/acs.orglett.8b01582
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Reductive Conversion of Acyl Fluorides via Ligand-Controlled Decarbonylation

Abstract: Ligand-controlled non-decarbonylative and decarbonylative conversions of acyl fluorides were developed using a Pd(OAc)/EtSiH combination. When tricyclohexylphosphine (PCy) was used as the ligand, aldehydes were obtained as simple reductive conversion products. The use of 1,2-bis(dicyclohexylphosphino)ethane (CyP(CH)PCy, DCPE) as the ligand, however, favored the formation of hydrocarbons, which are decarbonylative reduction products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(47 citation statements)
references
References 53 publications
2
40
0
4
Order By: Relevance
“…[14] Soon after, the same group reported an ickel-catalyzed decarbonylative borylation of acid fluorides 4 (Scheme 5). [17] In the presence of the monodentate PCy 3 ligand (L2), acid fluorides 1 were converted into the corresponding aldehydes 14 without decarbonylation. Ther eaction proceeds in moderate to excellent yields with good functional group tolerance;for example,anester group in para position remained untouched.…”
Section: Methodsmentioning
confidence: 99%
“…[14] Soon after, the same group reported an ickel-catalyzed decarbonylative borylation of acid fluorides 4 (Scheme 5). [17] In the presence of the monodentate PCy 3 ligand (L2), acid fluorides 1 were converted into the corresponding aldehydes 14 without decarbonylation. Ther eaction proceeds in moderate to excellent yields with good functional group tolerance;for example,anester group in para position remained untouched.…”
Section: Methodsmentioning
confidence: 99%
“…With the optimized condition in hand (entry 16 in Table ), the substrate scope was surveyed (Scheme ). Acyl fluorides were readily prepared from the corresponding carboxylic acids or acyl chlorides . It was found that acyl fluorides with an extended‐conjugated system ( 1 a , c , d ) reacted without difficulty, providing stannylation products in 77–89% isolated yields.…”
Section: Methodsmentioning
confidence: 99%
“…Bemerkenswert ist, dass das im Laufe des Prozesses gebildete Fluorid als milde Base wirkt und die Organoboronat-Zwischenstufen aktiviert. [17] In Gegenwart des einzähnigen PCy 3 -Liganden (L2)w urden die Säurefluoride 1 ohne Decarbonylierung in die entsprechenden Aldehyde 14 umgewandelt. Eine ähnliche Strategie wurde fürd ie decarbonylierende Methylierung und Ethylierung von Säurefluoriden mit Lewis-saurem Tr imethyl-oder Tr iethylboran und einem sehr ähnlichen Katalysesystem (Ni-(cod) 2 /dppe) angewendet, allerdings mit geringerer Anwendungsbreite.…”
Section: Methodsunclassified